Investigating Blended Learning Effects toward Students’ Literacies for Higher Education Setting - Ratnawati Ratnawati; Wawan Tarwana (Ethical Lingua: Journal of Language Teaching and Literature, 2018)
The present study aims at investigating blended learning effects towards students’ accomplishment in terms of participants’ literacies in terms of reading and writing score and their motivation of attending the model of learning. It employed experimental study which concerned on two groups pre-test post- test research design to find out students’ progress before and after blended learning application. Furthermore, two kinds of test; reading and writing test also distributed to the experimental and control groups which are also supported to five Likert scale questionnaires. The data found indicates that the participants had got progress in both writing and reading tests, evenly positive perspectives also expressed toward applying blended learning in classroom practices. The study specially implies recommendation for further pedagogical application in English classroom practices and educational context at general.